PERAN PENDIDIKAN ISLAM NON-FORMAL DALAM MITIGASI KONFLIK SOSIAL PADA MASYARAKAT PLURAL: STUDI DI DESA BALONGTUNJUNG GRESIK - Muhammad Makinun Amin; Muhammad Najib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of non-formal Islamic education in mitigating social conflict within a pluralistic community in Balongtunjung Village, Gresik Regency. The background of this study is rooted in the high potential for social friction within a heterogeneous community, which necessitates a values-based preventive approach. The study employs a qualitative approach with a case study design to deeply understand the naturalistic social-religious dynamics at play. Data were collected through observation, in-depth interviews, and documentation of religious figures and community members involved in religious activities. Data analysis was conducted interactively through the stages of data condensation, data presentation, and drawing conclusions using triangulation techniques to ensure the validity of the findings. The results of the study indicate that non-formal Islamic education, through Friday sermons, majelis taklim, and religious study sessions, serves as an effective social mechanism in mitigating potential conflicts and strengthening social cohesion. From a conflict theory perspective, these practices function as a safety valve that prevents the escalation of open conflict. Meanwhile, within the framework of social capital, non-formal education contributes to building trust, social networks, and reciprocal norms that support the creation of social harmony. These findings confirm that non-formal Islamic education serves not only as a means of transmitting religious values, but also as a strategic instrument in building sustainable community-based peace.